Tenure insecurity, climate variability, and renting-out decisions among female smallholder farmers in Ethiopia - Wisdom Akpalu; Mintewab Bezabih (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2014)
Land tenure arrangements in Africa are generally skewed in favour of males. Compared to males, female plot owners face complex sets of constraints and systemic high tenure insecurity which culminate in low yields. In order to obtain better returns, some females rent their plots to males, but risk losing the plots to their tenants. A model has been constructed to explain rentingout decisions of female small landholders, an issue largely ignored in the agricultural economics literature. The results, based on a survey of female landholders in Ethiopia, highlight the factors that explain renting-out decisions.
Keywords: D2; Q12; Q15; 330; climate variability; female-headed households; productivity; tenure insecurity